UMP honored for efforts in Biodiversity- Biotechnology Strategic Action Plan - UMP, PNC
Universiti Malaysia Pahang (UMP) received a Certificate of Appreciation from the State Government of Pahang in its efforts to chart out the State’s Biodiversity-Biotechnology Strategic Action Plan – which was officially launched by the country’s Deputy Prime Minister, Tan Sri Muhyiddin Mohd Yassin – at the Sultan Haji Ahmad Shah’s Silver Jubilee Hall in Kuantan, Pahang, on August 9, 2010.